The scene of disenchantment in A tango Abierto by Ana María del Río (ALPHA. Journal of Arts, Literature and Philosophy, 2000)
In several reviews, it has been indicated that A Tango Abierto 1996 by Ana María del Río 1948 is one of the most relevant novels of Chile in the 90s. With this book, Ana María del Río reconfirms herself as a key figure of the so-called generation of the 80s. , which includes Chilean writers born approximately in the 1950s, whose first texts in some cases began to be published in the middle of the military regime (1973 - 1989)